2016
DOI: 10.3892/etm.2016.3185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroacupuncture on gastric interstitial cells of Cajal in a rat model of diabetic gastroparesis

Abstract: Abstract. The aim of the present study was to observe the effect of electroacupuncture (EA) on the gastric interstitial cells of Cajal (ICCs) in a rat model of diabetic gastroparesis (DGP). The gastric tissues were collected from 75 rats, which had been divided into three equal groups (n=25/group): Blank, model and EA. Hematoxylin and eosin and immunohistochemical staining were used to observe the cellular morphology and distribution of c-kit-positive gastric ICCs; light microscopy was used to count the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Moreover, in the spatial structure, ICC-AP has also been found to have a closer relationship to the resident macrophages in muscularis [ 11 ]. It has been proposed that EA might help to reverse the pathological changes of ICC in diabetic rats [ 12 ]. Our previous study found the accelerative effects of gastric emptying by low- and high-frequency EA in diabetic rats; these may be attributed to the nearly unbroken ICC networks [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the spatial structure, ICC-AP has also been found to have a closer relationship to the resident macrophages in muscularis [ 11 ]. It has been proposed that EA might help to reverse the pathological changes of ICC in diabetic rats [ 12 ]. Our previous study found the accelerative effects of gastric emptying by low- and high-frequency EA in diabetic rats; these may be attributed to the nearly unbroken ICC networks [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…A reduced density of Interstitial cell of Cajal (ICC) is the most prominent cellular abnormality in both idiopathic and diabetic gastroparesis, and it provides a rational basis for the genesis of dysrhythmia in gastroparesis . EA was reported to reverse the pathological changes of gastric ICCs in a rodent model of diabetic gastroparesis …”
Section: Discussionmentioning
confidence: 99%
“…During the 13 w of the experiment, the rats with random blood glucose level of ≤ 16.7 mmol/L were removed from the experiment. Success criteria of the DGP model were as follows [14]: the blood glucose level to be ≥ 16.7 mmol/L; the general conditions and stool characteristics of the rats to be significantly different from the blank group; the rate of gastric emptying and small intestinal propulsion rate in rats to be significantly different from the blank group.…”
Section: Modelling Methods and Evaluationmentioning
confidence: 99%